PENERAPAN SISTEM AKUNTANSI PADA PT IFA ABDUL RAZAQ - Sephia Sephia; Siti Linda Mulyana; Syifa Azkia Marwah (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Accounting information systems have developed into a crucial component in the financial management of an organization, not only as a means of recording transactions but also as a strategic instrument that supports the success of business activities. This study aims to provide a comprehensive overview of how the accounting system is implemented, from recording to preparing financial reports, as well as evaluating the effectiveness of the system used. This research uses a qualitative method with the collection technique is an interview. The credit sales accounting system at PT IFA Factori includes processes ranging from order receipt, production, shipping, to settlement of customer receivables. The purchasing system involves raw material procurement procedures that are organized through documents such as Purchase Orders (PO) and inventory reports. The inventory system focuses on recording stocks of raw materials and finished goods to support production efficiency. In practice, PT IFA Factori still uses a manual Excel-based system, which often causes problems such as data discrepancies and process delays. This report recommends the use of integrated accounting software to improve accuracy, efficiency, and transparency in the company's financial management.